Multiscale Nature of Atmospheric Rivers - Chanil Park; Seok‐Woo Son; Bin Guan (Geophysical Research Letters, 2023)
Abstract This study provides evidence for the multiscale nature of atmospheric rivers (ARs) by differentiating them based on high‐ (HF) and low‐frequency (LF) moisture transports. The HF‐dominant ARs exhibit migratory behavior as they are typically accompanied by extratropical cyclones. Their spatial distribution is seasonally synchronized with midlatitude storm activity. On the other hand, the LF‐dominant ARs stay in place as they are associated with quasi‐stationary circulation. They prevail in the subtropical monsoon regions in the summer hemisphere. The ARs are often jointly affected by HF and LF processes. Such intermediate ARs are frequently observed along the poleward boundary of subtropical highs. The latter two AR types are locally more persistent than the HF‐dominant ARs, implying the importance of LF dynamics in long‐lasting AR impacts. We suggest that multiscale analysis of ARs will offer valuable insights into their diversity and hydrological impacts.